Olive orchard intensification compromises soil water erosion control in a semi-arid environment - Luciano Gristina; Ettore Barone; Riccardo Scalenghe (PLoS ONE, 2026)
Olive cultivation is a key component of Mediterranean agriculture. Super-high-density (SHD) hedgerow orchards are expanding because they enable mechanization and early yields, yet their environmental impacts on semi-arid slopes remain insufficiently studied. We quantified soil erosion in a six-year-old SHD olive orchard in southwestern Sicily (15.6% slope) using δ 13 C depth profiles and erosion-pole height measurements, and we estimated the RUSLE cover-management factor (C) from field data and Sentinel-2 NDVI. The SHD orchard exhibited mean erosion of 29.4 Mg ha ⁻ ¹ yr ⁻ ¹, comparable to vineyards and markedly higher than rates reported for traditional olive systems. Canopy architecture provided ~38% ground cover, leaving ~62% bare soil, and frequent downslope tillage likely amplified rill formation and sediment redistribution. Independent methods converged on similar C factors (0.38–0.39), indicating limited erosion control relative to traditional orchards. These site-specific results suggest that SHD orchards established on semi-arid slopes can substantially increase soil erosion risk. Conservation practices such as permanent cover crops, mulching/pruning-residue retention, and contour-aligned management could reduce erosion while maintaining productivity..